Biomechanical, cardiorespiratory, metabolic and perceived responses to electrically assisted cycling. - Sperlich, Billy; Zinner, Christoph; Hébert-Losier, Kim; Born, Dennis-Peter; Holmberg, Hans-Christer (Springer, 2012)
The article can be downloaded here: DOI 10.1007/s00421-012-2382-0 The aims of the present study were to characterize the effects of cycling in varying terrain with the assistance of an electric motor with respect to (1) power output, velocity, and electromyography (EMG) signals; (2) cardiorespiratory parameters; (3) energy expenditure (EE); (4) rate of perceived exertion (RPE) and enjoyment and to compare these effects with those of non-assisted cycling. Eight sedentary women (age: 38 ± 15 years, BMI: 25.3 ± 2.1 kg m(-2)) cycled 9.5 km on varying terrain (change in elevation: 102 m, maximum incline: 5.8 %) at their own pace, once with and once without motorized assistance, in randomized order. With electrical assistance, the mean power output (-29 %); EMG patterns of the m. biceps femoris (-49 %), m. vastus lateralis (-33 %), m. vastus medialis (-37 %), and m. gastrocnemius medialis (-29 %); heart rate (-29.1 %); oxygen uptake (-33.0 %); respiratory exchange ratio (-9.0 %); and EE (-36.5 %) were all lower, whereas the mean cycling speed was higher (P lt. 0.05) than that without such assistance. In addition, following assisted exercise the mean blood lactate concentration and RPE were lower (P lt. 0.05) and ratings of enjoyment higher (P lt. 0.05). Moreover, motorized cycling was associated with (1) lower EMG with higher power output and speed; (2) less cardiorespiratory and metabolic effort; (3) lower respiratory exchange ratio; (4) lower RPE with more enjoyment; and (5) sufficient EE, according to present standards, to provide health benefits. Thus, electrically assisted cycling may represent an innovative approach to persuading reluctant sedentary women to exercise.
Keywords: Individualverkehr; Fahrradverkehr; Elektrofahrrad; Fahrradnutzung; Pedelec; Gesundheitsförderung; Studie